Protective effect of zinc oxide nanoparticles on spinal cord injury - Liu, Jia; Huang, Zhendong; Yin, Suhan; Jiang, Yanping; Shao, Longquan (Frontiers in Pharmacology, 2022)
The microenvironmental changes in the lesion area of spinal cord injury (SCI) have been extensively studied, but little is known about the whole-body status after injury. We analyzed the peripheral blood RNA-seq samples from 38 SCI and 10 healthy controls, and identified 10 key differentially expressed genes in peripheral blood of patients with SCI. Using these key gene signatures, we constructed a precise and available neural network diagnostic model. More importantly, the altered transcriptome profiles in peripheral blood reflect the similar negative effects after neuronal damage at lesion site. We revealed significant differential alterations in immune and metabolic processes, therein, immune response, oxidative stress, mitochondrial metabolism and cellular apoptosis after SCI were the main features. Natural agents have now been considered as promising candidates to alleviate/cure neuronal damage. In this study, we constructed an in vitro neuronal axotomy model to investigate the therapeutic effects of zinc oxide nanoparticles (ZnO NPs). We found that ZnO NPs could act as a neuroprotective agent to reduce oxidative stress levels and finally rescue the neuronal apoptosis after axotomy, where the PI3K-Akt signaling probably be a vital pathway. In conclusion, this study showed altered transcriptome of peripheral blood after SCI, and indicated the neuroprotective effect of ZnO NPs from perspective of oxidative stress, these results may provide new insights for SCI diagnosis and therapeutics.